73.3k views
4 votes
Please help with this question! I was given the answer but wasn’t sure how it got to that answer

Please help with this question! I was given the answer but wasn’t sure how it got-example-1

1 Answer

1 vote

Answer:

Step-by-step explanation:

Given:


\begin{gathered} g(x)=-x^2-ax+3 \\ g(-2)=-9 \end{gathered}

It is given that g(-2)=-9, so it means that x=-2. We substitute x=-2 into -x^2-ax+3 to get the value of a.


undefined

User Cuh
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.